OPTIMIZING NODE.JS APPLICATION PERFORMANCE THROUGH MAIN THREAD OFFLOADING - Отыншин, Данияр (МЕЖДУНАРОДНЫЙ ЖУРНАЛ ИНФОРМАЦИОННЫХ И КОММУНИКАЦИОННЫХ ТЕХНОЛОГИЙ, 2023)
Node.js is a JavaScript runtime environment that allows you to run JavaScript code outside of a web browser. It works by using a single thread to handle multiple requests using a callback-based event loop. This means that Node.js operates in an event-driven, non-blocking I/O model. One potential weak point of Node.js is that it is designed to be a single-threaded runtime environment, which means that it may not be the best choice for applications that require a high degree of parallelism or multi-threading. While Node.js can handle multiple I/O operations simultaneously through its event-driven architecture, it can struggle with CPU-bound tasks that require heavy computation. This academic article investigates the concept of "offloading" the main thread in Node.js, which refers to the process of delegating heavy computational tasks to worker threads to improve the overall performance and responsiveness Node.js application. The article provides a comprehensive analysis of different techniques for offloading the main thread, such as using worker threads, child processes, and cluster modules. It also explores the potential trade-offs and performance implications of each technique, and provides recommendations for selecting the most suitable approach for different use cases. The article highlights the importance of optimizing the use of CPU resources and avoiding blocking the event loop, which can lead to degraded performance and poor user experience. It also emphasizes the need for careful monitoring and profiling of Node.js applications to identify performance bottlenecks and optimize the use of available resources. Overall, this article provides valuable insights and practical recommendations for developers and system architects who want to improve the performance and scalability of their Node.js applications by unloading the main thread.